Localization of Melanin in Conidia of Alternaria alternata Using Phage Display Antibodies - Raffaella Carzaniga; Daniela Fiocco; Paul Bowyer; Richard J. O'Connell (Molecular Plant-Microbe Interactions, 2002)
Melanins derived from 1,8-dihydroxynaphthalene (DHN) are important for the pathogenicity and survival of fungi causing disease in both plants and animals. However, precise information on their location within fungal cell walls is lacking. To obtain antibodies for the immunocytochemical localization of melanin, 83 phage antibodies binding to 1,8-DHN were selected from a naive semisynthetic single-chain Fv (scFv) phage display library. Sequence analysis of the heavy chain binding domains of 17 antibodies showed a high frequency of positively charged amino acids. One antibody, designated M1, was characterized in detail. M1 bound specifically to 1,8-DHN in competitive inhibition enzyme-linked immunosorbent assays, showing no cross-reaction with nine structurally related phenolic compounds. Epitope recognition required two hydroxyl groups in a 1,8 configuration. M1 also bound to naturally occurring melanin isolated from mycelia of Alternaria alternata, suggesting that epitopes remain accessible in polymerized melanin. Transmission electron microscopy-immunogold labeling, using M1 in the form of soluble scFv fragments, showed that melanin was located in the septa and outer (primary) walls of wild-type A. alternata conidia, but not those of an albino mutant, AKT88-1. The M1 antibody provides a new tool for detecting melanized pathogens in plant and animal tissues and for precisely mapping the distribution of the polymer within spores, appressoria, and hyphae.